Effects of aging procedures on the topographic surface, structural stability, and mechanical strength of a ZrO2-based dental ceramic - Cotes, Caroline [UNESP]; Arata, Anelyse [UNESP]; Melo, Renata M. [UNESP]; Bottino, Marco A. [UNESP]; Machado, Joao P. B.; Souza, Rodrigo O. A. (Elsevier B.V., 2014)
Objective. To determine the effects of different aging methods on the degradation and flexural strength of yttria-stabilized tetragonal zirconia (Y-TZP)Methods. Sixty disc-shaped specimens (0, 12 mm; thickness, 1.6 mm) of zirconia (Vita InCeram 2000 YZ Cubes, VITA Zahnfabrik) were prepared (ISO 6872) and randomly divided into five groups, according to the aging procedures (n=10): (C) control; (M) mechanical cycling (15,000,000 cycles/3.8 Hz/200N); (T) thermal cycling (6,000 cycles/5-55 degrees C/30 s); (TM) thermomechanical cycling (1,200,000 cycles/3.8 Hz/200N with temperature range from 5 C to 55 C for 60s each); (AUT) 12h in autoclave at 134 degrees C/2 bars; and (STO) storage in distilled water (37 degrees C/400 days). After the aging procedures, the monoclinic phase percentages were evaluated by X-ray diffraction (XRD), and topographic surface analysis was performed by 3D profilometry. The specimens were then subjected to biaxial flexure testing (1 mm/min, load 100 kgf, in water). The biaxial flexural strength data (MPa) were analyzed by 1-way ANOVA and Tukey's test (alpha = 0.05). The data for monoclinic phase percentage and profilometry (Ra) were analyzed by Kruskal-Wallis and Dunn's tests.Results. ANOVA revealed that flexural strength was affected by the aging procedures (p = 0.002). The M (781.6 MPa) and TM (771.3 MPa) groups presented lower values of flexural strength than did C (955 MPa), AUT (955.8 MPa), T (960.8 MPa) and STO (910.4 MPa). The monoclinic phase percentage was significantly higher only for STO (12.22%) and AUT (29.97%) when compared with that of the control group (Kruskal-Wallis test, p = 0.004). In addition, the surface roughnesses were similar among the groups (p = 0.165).Signcance. Water storage for 400 days and autoclave aging procedures induced higher phase transformation from tetragonal to monoclinic; however, they did not affect the flexural strength of Y-TZP ceramic, which decreased only after mechanical and thermomechanical cycling. (C) 2014 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Yttria-stabilized tetragonal zirconia; Flexural strength; Phase transformation